Energy and exergy analysis of a flat plate solar collector using different sizes of aluminium oxide based nanofluid. (1st October 2016) - Said, Z.; Saidur, R.; Rahim, N.A.
Abstract: Growing dependence of industry and technology on fossil energy and increasing population encounters all countries with challenge of energy for future. Therefore, investigation about renewable energies, particularly solar energy is considered. The use of nanofluids in solar collectors offers better performance, as they are very efficient in transporting heat even under small temperature difference. The effect of Aluminium oxide (Al2 O3 )–water nanofluid, as working fluid, is used to evaluate the thermal efficiency of a flat plate solar collector, experimentally. A volume fraction of 0.1% for size of (13 nm and 20 nm) nanoparticles, respectively was used for this study. The mass flow rates of the nanofluid varied from 0.5 to 1.5 kg/min. Experiments were carried out using a stable nanofluid. The stability of nanofluid was obtained by controlling the pH of the solution. An ASHRAE Standard 93-2010 (R2014) was used to analyze efficiency of the solar collector. The results reflect the contribution and significance of each of these parameters to the collector overall energetic and exergetic efficiencies. Two different sizes of Al2 O3 –water nanofluid 13 nm and 20 nm are examined, and results show that 13 nm Al2 O3 nanofluid shows higher thermal conductivity enhancement and efficiency, compared to that of 20 nm Al2 O3 nanofluid and water. Al2 O3 –H2 O (13 nm) nanofluid with 0.1% volume fraction and at a flow rate of 1.5 kg/min showed the highest energy efficiency of about 73.7%, compared to Al2 O3 –H2 O (20 nm) nanofluid, which showed an energy efficiency of 70.7%. Critical point of Al2 O3 –water nanofluid is also presented, which has not be reported in literature according to author's knowledge, which also shows the novelty of this work. Highlights: Thermal conductivity is higher for 13 nm Al2 O3 –H2 O nanofluid compared to water. Performance improved with 13 nm Al2 O3 –H2 O nanofluid compared to water. Energy efficiency improved by 73.7% for 13 nm Al2 O3 nanoparticle. Exergy efficiency is enhanced by up to 20.3% for 13 nm Al2 O3 nanoparticle.